2017
DOI: 10.1038/s41598-017-03994-1
|View full text |Cite
|
Sign up to set email alerts
|

A subset of cerebrovascular pericytes originates from mature macrophages in the very early phase of vascular development in CNS

Abstract: Pericytes are believed to originate from either mesenchymal or neural crest cells. It has recently been reported that pericytes play important roles in the central nervous system (CNS) by regulating blood-brain barrier homeostasis and blood flow at the capillary level. However, the origin of CNS microvascular pericytes and the mechanism of their recruitment remain unknown. Here, we show a new source of cerebrovascular pericytes during neurogenesis. In the CNS of embryonic day 10.5 mouse embryos, CD31+F4/80+ he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 64 publications
1
75
1
Order By: Relevance
“…They are located in perivascular spaces, between endothelial and glial basement membranes and are involved in sampling debris and dying cells, the maintenance of endothelial cells, the BBB and capillaries, and the regulation of vascular constriction . Moreover, CD31 + F4/80 + macrophages, which are derived from embryonic hematopoiesis, differentiate into a subset of cerebrovascular pericytes, which impact on BBB function . Studies using transgenic mice with different degrees of pericyte deficiency showed that pericytes inhibit the expression of molecules that increase vascular permeability …”
Section: Introductionmentioning
confidence: 99%
“…They are located in perivascular spaces, between endothelial and glial basement membranes and are involved in sampling debris and dying cells, the maintenance of endothelial cells, the BBB and capillaries, and the regulation of vascular constriction . Moreover, CD31 + F4/80 + macrophages, which are derived from embryonic hematopoiesis, differentiate into a subset of cerebrovascular pericytes, which impact on BBB function . Studies using transgenic mice with different degrees of pericyte deficiency showed that pericytes inhibit the expression of molecules that increase vascular permeability …”
Section: Introductionmentioning
confidence: 99%
“…Macrophages may also directly contribute to vascular stabilization as perivascular macrophages are highly abundant around blood vessels (He et al, 2016). Interestingly, embryonic macrophages have been observed to transdifferentiate into pericytes in the developing mouse brain, indicating an additional direct contribution of macrophages to vascular maturation (Yamamoto et al, 2017). Other stud- (Zhang et al, 2012).…”
Section: Maturationmentioning
confidence: 99%
“…In particular, pericytes are a unique cell type that participates into the formation and maintenance of the blood-brain barrier (BBB), together with vascular endothelial cells and astrocytes, at the border between the brain parenchyma and a dense network of microvasculature within the brain (Sweeney, Ayyadurai, & Zlokovic, 2016). Recent studies have proposed that a subset of pericytes derive from peripheral macrophages migrate into the brain (Sweeney et al, 2016;Yamamoto et al, 2017). Yet, given the recent discovery of the molecular heterogeneity of pericytes, the origin of pericytes in various brain regions need to be further investigated (Sweeney et al 2016).…”
Section: Box 1 Impacts Of Non-neuronal/glial Cell Types On Postnatal mentioning
confidence: 99%